Interventional Imaging Techniques as Alternative to Surgery of the Foot and Ankle - Burke, Christopher J.; Walter, William R.; Adler, Ronald S. (Seminars in Musculoskeletal Radiology, 2022)
A variety of foot and ankle pathologies can impair patient's daily activities, ultimately requiring surgical management. However, with improvements in image-guided intervention, the joints, soft tissues, and osseous structures may be accessible using various percutaneous techniques as a potential alternative therapeutic tool, avoiding the need for surgery with its associated risks and morbidity. This article discusses the potential range of image-guided interventional treatments. Injections, aspiration, biopsies, cryoablation, and radiofrequency ablation are described. Newer novel treatments are also covered. Finally, the common pathologies of Morton's neuroma, Achilles tendinopathy, and plantar fasciitis are addressed.
Keywords: foot/ankle pathology; injection; aspiration; ablation; ultrasonography